Städtisches Museum Abteiberg Mönchengladbach : Illustrations and Comments. - Städtisches Museum Abteiberg, Mönchengladbach; Jakubowski, Hans Dieter; Kersting, Hannelore; Loers, Veit; Smidt, Thorsten (Mönchengladbach : Städtisches Museum Abteiberg, 2002)
Althoff, Kai ; Andre, Carl ; Arman ; Beuys, Joseph ; Boltanski, Christian ; Broodthaers, Marcel ; Buren, Daniel ; Calder, Alexander ; Chamberlain, John ; Charlton, Alan ; Coenen, Otto ; Fontana, Lucio ; Förg, Gunther ; Hains, Raymond ; Heckel, Erich ; Heerich, Erwin ; Horn, Rebecca ; Horn, Roni ; Jawlensky, Alexej von ; Judd, Donald ; Kelley, Mike ; Kippenberger, Martin ; Kirchner, Ernst Ludwig ; Klein, Yves ; Kounellis, Jannis ; Kupka, Frantisek ; van der Leck, Bart ; Long, Richard ; Mack, Heinz ; Manzoni, Piero ; Marioni, Joseph ; Matta-Clark, Gordon ; Merz, Mario ; Morellet, François ; Müller, Christopher ; Nauen, Heinrich ; Nauman, Bruce ; Oehlen, Albert ; Oldenburg, Claes ; Palermo, Blinky ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Polke, Sigmar ; Man Ray ; Rehberger, Tobias ; Rentmeister, Thomas ; Richter, Gerhard ; Roth, Dieter ; Rückriem, Ulrich ; Ryman, Robert ; Sander, Karin ; Schlemmer, Oskar ; Schwitters, Kurt ; Segal, George ; Seiwert, Franz Wilhelm ; Serra, Richard ; Sonnier, Keith ; Spoerri, Daniel ; Tinguely, Jean ; Umberg, Günter ; Villeglé, Jacques ; Virnich, Thomas ; Vordemberge-Gildewart, Friedrich ; Warhol, Andy ; Weiner, Lawrence ; Wesselmann, Tom ; West, Franz
Engels
boek